Design and Development of IoT-Based Mobile Application for Heart Rate and Body Temperature Monitoring - Den Bintang Restu Satria Shandra; Anita Fira Waluyo (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2025)
The rapid development of Internet of Things (IoT) technology has influenced many fields, especially healthcare delivery systems. This paper will analyze the effect of IoT-based mobile applications on the quality of healthcare services through real-time patient monitoring. The application developed in this study was used to monitor vital signs heart rate and body temperature using sensors attached to mobile devices. The research methodology includes system architecture design and implementation with MAX30102, DS18B20, and MLX90614 sensors where the ESP32 microcontroller acts as the main integration platform. The application development was done using Android Studio and Flutter frameworks. User testing showed significant improvements in the speed at which critical conditions are detected among patients and also in the time taken by healthcare providers to respond to such situations. User satisfaction ratings indicated high acceptance levels, thus proving a large potential market for digital healthcare. Results from this study also proved that IoT-mobile application integration can uplift standards in healthcare services while providing a practical solution for modern-day medical practice.